Understanding the effects of real-time head position feedback on postural sway in terms of changes in underlying deterministic and stochastic dynamical processes - Steven J. Harrison; Benjamin De Bari; Ryan Poutre; Jeffrey M. Kinsella-Shaw (PLoS ONE, 2025)
Our perceptual systems detect information about how our body is moving relative to the surrounding environment. Such information is essential to our ability to maintain upright standing balance. Real-time postural feedback systems are technologies that appear to enhance our ability to detect information about the movements of our body, and as a consequence improve our capacity to control the posture of our body. Here we examine a system in which real-time measurements of head position were “felt” as changes in the intensity of vibration of tactors in a headband. Using this system, participants were able to stabilize their body posture, showing a reduction in the magnitude of head sway fluctuations of more than 40% under single and dual tasking conditions. To examine this effect, we used a dynamical model that assumes that observed magnitudes of postural fluctuations reflect combined effects of underlying deterministic and stochastic dynamical processes. We derived estimates of model parameters, λ and Q . λ measures attractor strength, it quantifies the influence of the deterministic process that cause postural fluctuations to tend to drift towards a desired state. Q measures noise, it quantifies the destabilizing effects of internal perturbations and background/physiological variability in the postural control system. We find that use of our head position feedback system led to marked increases in attractor strength. This increase in attractor strength was accompanied by a marked increase in noise. When we linearly increased the resolution of feedback—by narrowing the width of the tactor activation function—we observed an approximately linear increase in attractor strength together with a non-linear increase in noise. These results suggest that use of a real-time postural feedback systems can increase the stability of postural control, but that this benefit is limited by significant accompanying exacerbations of noise being introduced into the postural control system.